PERSEPSI ANAK MUDA KOTA DENPASAR TENTANG PARTAI SOLIDARITAS INDONESIA - Setiadi Guru, Febrianus; Bandiyah, Bandiyah; Jayanthi Mertha, A. A. Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2019)
ABSTRACT Thiswresearchqaimsuto know the perception.of youth in Denpasar City on Indonesian Solidarity Party seen from the performance of Indonesian Solidarity Party in doing their part as political party in a democratic country.This research uses the conceptual function of political parties by Miriam Budiardjoand uses quantitative descriptive method. Samplingztechniquezthatziszused inrthistrresearchrrisspurposiveffsampling. This research shows that the average of youth in Denpasar City about Indonesian Solidarity Party as a means of political communication is 3,44, as a means of political sosialitation is 3,71, as a means of political recruitment is 3,64, and as a means of regulating conflict is 3,27. The overall total score is 3,51. Basedzon thatcfindings, itjcan bewconcludeddthatxthecyouth in Denpasar City has a good perception on Indonesian Solidarity Party. Key Words :Denpasar, Indonesian Solidarity Party, Perception, Youth